2023
DOI: 10.3390/pharmaceutics15092272
|View full text |Cite
|
Sign up to set email alerts
|

Optical Methods for Non-Invasive Determination of Skin Penetration: Current Trends, Advances, Possibilities, Prospects, and Translation into In Vivo Human Studies

Maxim E. Darvin

Abstract: Information on the penetration depth, pathways, metabolization, storage of vehicles, active pharmaceutical ingredients (APIs), and functional cosmetic ingredients (FCIs) of topically applied formulations or contaminants (substances) in skin is of great importance for understanding their interaction with skin targets, treatment efficacy, and risk assessment—a challenging task in dermatology, cosmetology, and pharmacy. Non-invasive methods for the qualitative and quantitative visualization of substances in skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 304 publications
0
11
0
Order By: Relevance
“…The efficiency of the carrier transportation was assessed using OCT, which was proven to be effective in determining the penetration and accumulation of particulate formulations in skin under native and non-destructive in vivo conditions. 89–91 This non-invasive imaging modality was also utilized further to monitor the process of the CP–CaCO 3 carriers’ degradation in skin. Previously, we have convincingly demonstrated that this method allows for a reliable assessment of hair follicle filling with the CaCO 3 carriers providing a strong correlation between the data obtained using OCT and the other investigation methods, including CLSM, 46,48,61 SEM, 46,61,92 and histological examination.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of the carrier transportation was assessed using OCT, which was proven to be effective in determining the penetration and accumulation of particulate formulations in skin under native and non-destructive in vivo conditions. 89–91 This non-invasive imaging modality was also utilized further to monitor the process of the CP–CaCO 3 carriers’ degradation in skin. Previously, we have convincingly demonstrated that this method allows for a reliable assessment of hair follicle filling with the CaCO 3 carriers providing a strong correlation between the data obtained using OCT and the other investigation methods, including CLSM, 46,48,61 SEM, 46,61,92 and histological examination.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of TPE‐FM over OPE‐FM is the reducing fluorescence background and photobleaching that improves signal‐to‐noise ratio and provides high lateral and axial resolution, contrast and image quality, and lower risk of cell damage. Due to the red to near infrared excitation wavelengths, it is possible to reduce light attenuation in the skin and increase imaging depth [49]. TPE‐FM allows studying various characteristics of fibroblasts, such as size and metabolic status, assessing the influence of the environment, virus, and other effects.…”
Section: Two‐photon Fmmentioning
confidence: 99%
“…CRM is useful for liquid samples/cultures analysis. The main disadvantage of CRM is that the light scattered by the cells is weak, and a long signal acquisition is required to obtain high‐quality images [154] that makes in vivo skin imaging impossible [49]. There are already prerequisites for developing CRM protocols for in vivo measurements, for instance, combining with skin optical clearing technique to enhance the image depth until papillary and reticular dermis [171].…”
Section: Raman Microspectroscopymentioning
confidence: 99%
See 2 more Smart Citations